An Analytical Survey of Attitude and Perception towards Gender Inequality and Discrimination of Higher Education Students - Vashishtha, Deeksha (Journal of Advanced Research in Humanities and Social Sciences; Vol 9 No 1 (2022): Journal of Advanced Research in Humanities and Social Sciences, 2022)
Gender inequality is a sociological problem because of unfair treatment in society between various genders. These dissimilarities are distinguished from biological factors, especially from differing reproductive roles in life. Attitude and perception toward gender discrimination are social phenomena. In this research paper researcher find out the attitude and perception of students towards gender discrimination and inequality. Descriptive Research (Survey method) applies to describe and interpret the study attitude and perception. UG and PG level students who are studying in District Bijnor will constitute the population of the study. For this analysis, mean, SD, t-test and ANOVA inferential statistics use for this research. The research used the Stratified Random Sampling technique employed for the selection of 200 student sample. According to the data analysis, all null hypotheses are rejected and the researcher finds out gender, area and subject of the stream are not affected by the attitude and perception of students. Gender discrimination and inequality is a sociological factor that society decides. How to cite this article:  Vashishtha D. An Analytical Survey of Attitude and Perception towards Gender Inequality and Discrimination of Higher Education Students. J  Adv Res Humani Social Sci 2022; 9(1): 1-5. DOI: https://doi.org/10.24321/2349.2872.202201